Transcranial direct current stimulation (tDCS) as a treatment for visual hallucinations: A case study. (December 2017) - Koops, Sanne; Sommer, Iris E.C.
Highlights: Transcranial direct current stimulation may ameliorate visual hallucinations. tDCS is a promising treatment option when antipsychotics fail or are not indicated. tDCS had maximum effect within 1 week, treatment prolongation had no benefit.